2012
DOI: 10.1016/j.imbio.2012.08.053
|View full text |Cite
|
Sign up to set email alerts
|

C5aR-dependent cell activation by physiological concentrations of C5a-desArg: Insights from a novel label-free cellular assay

Abstract: The complement anaphylatoxins C3a, C5a, and C5a desArg play critical roles in the induction of inflammation and the modulation of innate and acquired immune responses after binding to their G protein-coupled receptors, C3aR and C5aR. The role of C5a desArg in inducing cell activation has been often neglected, since the affinity of C5a desArg for C5aR has been reported to be much lower than that of C5a. We have used a novel label-free cellular assay to reassess the potential of C5a desArg to induce activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Interestingly, previous studies have suggested that the removal of terminal arginine (Arg 74 ) in C5a in-vivo by the action of a carboxypeptidase yields C5a des-Arg , and it displays significantly reduced binding affinity and potency at C5aR1 when tested using recombinant ligand 10,16,25,26 . The extensive interaction of Arg 74 in C5a with multiple residues in C5aR1 such as Tyr259 6.51 , Gly263 6.55 , Ile266 6.58 and Val287 7.38 , which are critical for stabilizing carboxyl-terminal conformation of C5a in the orthosteric pocket, and will be absent in case of C5a des-Arg , may help rationalize its lower potency at the receptor (Figure S10B).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, previous studies have suggested that the removal of terminal arginine (Arg 74 ) in C5a in-vivo by the action of a carboxypeptidase yields C5a des-Arg , and it displays significantly reduced binding affinity and potency at C5aR1 when tested using recombinant ligand 10,16,25,26 . The extensive interaction of Arg 74 in C5a with multiple residues in C5aR1 such as Tyr259 6.51 , Gly263 6.55 , Ile266 6.58 and Val287 7.38 , which are critical for stabilizing carboxyl-terminal conformation of C5a in the orthosteric pocket, and will be absent in case of C5a des-Arg , may help rationalize its lower potency at the receptor (Figure S10B).…”
Section: Resultsmentioning
confidence: 99%